153k views
4 votes
Consider the equation 3p – 7 + p = 13. What is the resulting equation after the first step in the solution?

A) p – 7 = 13 – 3p
B) 2p – 7 = 13
C) 3p – 7 = 13 – p
D) 4p – 7 = 13

2 Answers

5 votes

Answer:

D) 4p – 7 = 13

Explanation:

The first step is to combine like terms:

Combine 3p and p

3p – 7 + p = 13

3p + p – 7 = 13

4p – 7 = 13

This equation is the same as answer choice D, so our answer is correct.

User Panagiotis Vrs
by
4.8k points
4 votes
D you would add the two “p” together 3p+p that would result in 4p-7=13
User Gareth Farrington
by
5.2k points